2016
DOI: 10.3892/mmr.2016.4836
|View full text |Cite
|
Sign up to set email alerts
|

The hypoxia-mimetic agent CoCl2 induces chemotherapy resistance in LOVO colorectal cancer cells

Abstract: Hypoxia, which is an important factor that mediates tumor progression and poor treatment response, is particularly associated with tumor chemoresistance. However, the molecular mechanisms underlying hypoxia-induced colorectal cancer chemoresistance remain unclear. The present study aimed to explore the mechanism underlying hypoxia-induced chemotherapy resistance in LOVO colorectal cancer cells. LOVO cells were cultured in a hypoxic environment simulated by cobalt chloride (CoCl2), which is a chemical inducer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…While it is difficult to control oxygen levels precisely to simulate hypoxic condition in cell culture, various in vitro models of neuronal hypoxia have been provided using divalent cations such as cobalt (Montel et al, 2007; Hang et al, 2009; Lopez-Sánchez et al, 2014; Yang et al, 2016). Cobalt have been applicable to mimic hypoxic conditions in cultured cells because they activate hypoxic signals by stabilizing the expression of hypoxia-inducible factor-1 alpha (HIF-1α), an O 2 -regulated transcriptional activator.…”
Section: Discussionmentioning
confidence: 99%
“…While it is difficult to control oxygen levels precisely to simulate hypoxic condition in cell culture, various in vitro models of neuronal hypoxia have been provided using divalent cations such as cobalt (Montel et al, 2007; Hang et al, 2009; Lopez-Sánchez et al, 2014; Yang et al, 2016). Cobalt have been applicable to mimic hypoxic conditions in cultured cells because they activate hypoxic signals by stabilizing the expression of hypoxia-inducible factor-1 alpha (HIF-1α), an O 2 -regulated transcriptional activator.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effect was more pronounced under hypoxia. This would agree with previous studies suggesting the role of HIF-1α in Pgp expression (5)(6)(7). Considering this, to directly examine the role of HIF-1α in Pgp upregulation after exposure to microenvironmental stressors, HIF-1α was silenced using siHIF-1α relative to the non-targeting control (siNC) in KBV1 (+Pgp) cells (Fig.…”
Section: Micro-environmental Tumor Stressors Play a Role In The Exprementioning
confidence: 47%
“…Furthermore, we demonstrate that stressors characteristic of the tumor micro-environment greatly affected drug resistance not only by upregulating Pgp, but also by re-localizing Pgp to lysosomes. This investigation also showed that stressors up-regulate HIF-1α, which is involved in the transcriptional up-regulation of Pgp (5)(6)(7)32).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, caspase 12 as a key protein activated by ER stress eventually activates caspase 3 to induce the cellular apoptosis. Cobalt is appropriate for mimicking hypoxic conditions in cultured cells due to its ability to activate hypoxic signals by stabilizing the expression of hypoxia-inducible factor-1 alpha [42,43]. Thus, CoCl 2 was used to mimic hypoxic conditions in VSC4.1 motor neurons.…”
Section: Discussionmentioning
confidence: 99%